2010
DOI: 10.1016/j.ntt.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Developmental selenomethionine and methylmercury exposures affect zebrafish learning

Abstract: Methylmercury (MeHg) is a ubiquitous environmental pollutant and has been shown to affect learning in vertebrates following relatively low exposures. Zebrafish were used to model long-term learning deficits after developmental MeHg exposure. Selenomethionine (SeMet) co-exposure was used to evaluate its role in neuroprotection. Embryos were exposed from 2-24 hours post fertilization to (1) MeHg without SeMet, (2) SeMet without MeHg and (3) in combination of MeHg and SeMet. In case (1), the levels of MeHg were 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 72 publications
3
37
0
Order By: Relevance
“…For example, mercury can negatively affect vision (Ventura et al, 2005;Cavalleri et al, 1995), as well as learning and memory (Smith et al, 2010;Falluel-Morel et al, 2007), and therefore could disrupt an association between the pattern of sensory input produced by the magnetic field and the visual surrounding. Moreover, our study can exclude that the turtles have even more general defects, which we did not detect in the motor-related performance tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mercury can negatively affect vision (Ventura et al, 2005;Cavalleri et al, 1995), as well as learning and memory (Smith et al, 2010;Falluel-Morel et al, 2007), and therefore could disrupt an association between the pattern of sensory input produced by the magnetic field and the visual surrounding. Moreover, our study can exclude that the turtles have even more general defects, which we did not detect in the motor-related performance tests.…”
Section: Discussionmentioning
confidence: 99%
“…It can bio-accumulate over an animal's lifetime and be transferred from mother to offspring (Bergeron et al, 2010). A variety of studies have shown negative effects of mercury exposure on reproduction (Barr and Service, 1986;Bergeron et al, 2011;Hammerschmidt et al, 2002;Brasso and Cristol, 2008) and behaviour (Chin et al, 2013;Smith et al, 2010) in vertebrates. Investigating whether mercury exposure affects responses to the Earth's magnetic field is of particular importance not only because of the wide spread effects of mercury toxicity on the vertebrate nervous system (Wolfe et al, 1998), but also because the effects of mercury may be specific to the magnetoreception mechanism(s) that mediate these responses.…”
Section: Introductionmentioning
confidence: 99%
“…Neurodevelopmental exposure to bisphenol A, methylphenidate, selenomethionine, methylmercury or ethanol resulted in learning deficits in adult zebrafish (Carvan et al, 2004;Levin et al, 2011;Saili et al, 2012;Smith et al, 2010). Blocking NMDA receptors by exposing zebrafish to MK-801 resulted in impaired memory which could be rescued by the applying currently available antipsychotic drugs (Seibt et al, 2011;Sison and Gerlai, 2011).…”
Section: Learning and Memorymentioning
confidence: 99%
“…[10][11][12][13][14][15][16] While many studies examined the behavioral effects of Pb 2 + using post-birth or post-hatch exposures, including during juvenile or adult stages, fewer studies investigated changes in adult behavior due to Pb 2 + exposures only during the earliest periods of embryonic or fetal development. 17,18 Such studies are important in that the effects of juvenile or adult exposures may vary depending on age of exposure or degree of sexual maturation [19][20][21][22] ; developmental exposures, however, have a greater potential for permanent, long-term behavioral changes, [23][24][25] possibly due to Pb 2 + -gene interactions or fundamental changes in neurodevelopment during the earliest stages of organ differentiation. [26][27][28] Social behavior, particularly agonistic interactions, has a strong sex-linked basis in mammals 29,30 but is more complicated in fishes because sex determination is not purely based on the presence of sex-linked chromosomes, for example, temperature, sex ratios, and pheromonal cues may be determinants of individual sex status.…”
Section: Introductionmentioning
confidence: 99%